The Implementation of State Defense Values to Strengthen Border Community in Dealing with The Threat of Proxy War: Case Study of Sungai Limau Village, Central Sebatik Sub-District, Nunukan District, North Kalimantan Province - wahyudi, wahyudi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
Conditions of border area village of Sungai Limau, District Central Sebatik Nunukan Regency, North Kalimantan province was geographically adjacent to the neighbour country Malaysia and the existence of two community groups who are different, both ethnically and religiously, have become challenges in the social life in Borderland area. From the aspect of Defense Studies, the dynamics could be potential targets of the Proxy War through the Border Region. Therefore, it is necessary to strengthen the implementation of Bela Negara (state defense) values to address it. This study aims to analyze the form in implementing the state defense values of the state defense in the border village of Sungai Limau in facing various challenges such as the susceptible threat of proxy war, using an analysis tool of the Bela Negara conception (State Defense) and Proxy War and Conception of Frontier Society. This study uses a qualitative method by collecting data obtains from interviews, observation, and literature. The result shows that the implementation of the state defense values among the frontier communities in Sungai Limau has the potential to be developed into power in the form of attitudes and practices of national and state awareness and place Pancasila as the state ideology and means of unifying societies that is reflected in the daily life. This can be a social capital to address the threats of proxy war in the border area. Keywords: State defense; Proxy War; Frontier Community.Â Â Â